2013
DOI: 10.1002/pro.2324
|View full text |Cite
|
Sign up to set email alerts
|

β‐Bulges: Extensive structural analyses of β‐sheets irregularities

Abstract: b-Sheets are quite frequent in protein structures and are stabilized by regular main-chain hydrogen bond patterns. Irregularities in b-sheets, named b-bulges, are distorted regions between two consecutive hydrogen bonds. They disrupt the classical alternation of side chain direction and can alter the directionality of b-strands. They are implicated in protein-protein interactions and are introduced to avoid b-strand aggregation. Five different types of b-bulges are defined. Previous studies on b-bulges were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 73 publications
1
30
0
1
Order By: Relevance
“…We then carried out RosettaDesign calculations (24) to favor amino acid identities and sidechain conformations with low-energy, tight packing and high sequence-structure compatibility. We hypothesized that β-bulge positions could be specified at the sequence level solely by changing the normal alternating pattern of polar and hydrophobic amino acids (more complex patterns are observed in native structures (see refs (19, 25) and fig. S4)) — in a β-bulge, unlike regular strands, two successive residues point in the same direction (Fig.…”
mentioning
confidence: 99%
“…We then carried out RosettaDesign calculations (24) to favor amino acid identities and sidechain conformations with low-energy, tight packing and high sequence-structure compatibility. We hypothesized that β-bulge positions could be specified at the sequence level solely by changing the normal alternating pattern of polar and hydrophobic amino acids (more complex patterns are observed in native structures (see refs (19, 25) and fig. S4)) — in a β-bulge, unlike regular strands, two successive residues point in the same direction (Fig.…”
mentioning
confidence: 99%
“…3 times more proteins with longer times than before). The MD protocol was the same as in the original paper (see [20,24] for details). These new data are used to evaluate the stability of the prediction quality.…”
Section: Resultsmentioning
confidence: 99%
“…Chan et al [33] have systematically classified β-bulges. A revised analysis by Craveur et al [34] describes how β-bulges impart irregularities in β-strand pairing by disrupting alternation of side-chains or terminate the β-strand. Our analysis showed that approximately 18-20 % of indents as well as edges have β-bulges (Table 1).…”
Section: Short Edge Vs Disprotmentioning
confidence: 99%